Mucinous tubular and spindle cell carcinoma of kidney: A clinicopathologic study of six cases - Mudassar Hussain; Nasir Ud Din; Muhammad Azam; Asif Loya (Wolters Kluwer Medknow Publications, 2012)
Background: Mucinous tubular and spindle carcinoma (MTSCC) of kidney is a rare, low-grade polymorphic tumor. Recent studies have described a wide morphology spectrum of this tumor. Aim: To report the clinico-pathologic features of six cases of MTSCC of kidney. Materials and Methods: Six cases of MTSCC of kidney were studied and literature was reviewed. Immunohistochemistry was done by Envision method. Results: The age of the patients ranged from 44 to 84 years (mean 58.5 years). Four patients were males and two were females. The tumor was located in the left kidney in four cases and in the right kidney in two cases. The tumor size ranged from 4.5 to 15 cm (mean 6.4 cm). All tumors exhibited an admixture of tubules, spindle cells, and mucinous stroma in variable proportions. Tubules were predominant in five cases and spindle cells in one case. Psammomatous calcifications, papillations, and necrosis were seen in two cases. Collections of foamy histiocytes were noted in four cases. Cytoplasmic vacuoles and osseous metaplasia were seen in one case each. All cases were Fuhrman's nuclear grade II. Five cases were of stage pT1, and one was pT3. All cases stained positive for alcian blue at pH 2.5. Immunohistochemical stain CK7 was positive in all cases and CD10 was positive in 1/1 case. All patients were alive and well at follow-up of 12-59 months (mean 33.5 months). No metastases were detected. Conclusions: We report six cases of MTSCC of kidney, a rare distinct variant of RCC, with a favorable prognosis. A male predominance was seen in our cases. MTSCC shares histologic and immunohistochemical overlap with papillary renal cell carcinoma (PRCC) and cytogenetic analysis should be performed in difficult cases to avoid a misdiagnosis.